Building Web Applications with UML - Conallen, Jim (Object Technology Ser., 1999)
Building Web Applications with UML is a guide to building robust, scalable, and feature-rich web applications using proven object-oriented techniques. Written for the project manager, architect, analyst, designer, and programmer of web applications, this book examines the unique aspects of modeling web applications with the Web Application Extension (WAE) for the Unified Modeling Language (UML). The UML has been widely accepted as the standard modeling language for software systems, and as a result is often the best option for modeling web application designs. The WAE extends the UML notation with semantics and constraints enabling developers to model web-specific architectural elements using the Rational Unified Process or an alternative methodology. Using UML allows developers to model their web applications as a part of the complete system and the business logic that must be reflected in the application. Readers will gain not only an understanding of the modeling process, but also the ability to map models directly into code. Key topics include: A basic introduction to web servers, browsers, HTTP, and HTML Gathering requirements and defining the system's use cases Transforming requirements into a model and then a design that maps directly into components of the system Defining the architecture of a web application with an examination of three architectural patterns describing architectures for thin web client, thick web client, and web delivery designs Modeling, at the appropriate level of abstraction and detail, the appropriate artifacts, including web application pages, page relationships, navigate routes, client-side scripts, and server-side generation Creating code from UML models using ASP and VBScript Client-side scripting using DHTML, Java Script, VBScript, Applets, ActiveX controls, and DOM Using client/server protocols including DCOM, CORBA/IIOP, and Java's RMI Securing a web application with SET, SSL, PGP, Certificates, and Certificate Authorities 0201615770B04062001.